2023
DOI: 10.3390/min13060742
|View full text |Cite
|
Sign up to set email alerts
|

Textural and Chemical Characters of Lean Grade Placer Monazite of Bramhagiri Coast, Odisha, India

Abstract: The present study aims to investigate the textural, mineralogical and geochemical characteristics of lean grade placer monazite from the Bramhagiri beach sand deposit to assess the possibility for its use in industrial applications. The bulk back dune sand deposit with 18 samples showed the elements uranium and thorium in traces, phosphorus and calcium in minor amounts, and alumina, silica and titanium in major amounts. Since apatite was absent in this placer deposit, P and Ca were attributed to monazite only.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The data given in Table 7 indicate that the monazite contains more cerium oxide, and hence, it can be concluded that the monazite of the Bramhagiri source is cerium monazite. This observation has been published by Deependra Singh et al in their study on the textural and chemical characteristics of lean-grade placer monazite of the Bramhagiri Coast, Odisha, India [32]. The rare earth element (REE) geochemistry of monazites of the Bramhagiri coastal sand deposit has been studied using the ICP method.…”
Section: Characterization Of Monazitementioning
confidence: 81%
See 3 more Smart Citations
“…The data given in Table 7 indicate that the monazite contains more cerium oxide, and hence, it can be concluded that the monazite of the Bramhagiri source is cerium monazite. This observation has been published by Deependra Singh et al in their study on the textural and chemical characteristics of lean-grade placer monazite of the Bramhagiri Coast, Odisha, India [32]. The rare earth element (REE) geochemistry of monazites of the Bramhagiri coastal sand deposit has been studied using the ICP method.…”
Section: Characterization Of Monazitementioning
confidence: 81%
“…In this second approach, instead of a high-tension separator, the flotation process has been attempted to recover fine-grained monazite. It is a known fact and industrially accepted that flotation is a process for fine-particle separation [27][28][29][30][31][32]. In view of this, an attempt is made in the present investigation to float monazite by using a flotation process.…”
Section: Judicious Combination Of Dry and Wet Processes To Recover Mo...mentioning
confidence: 99%
See 2 more Smart Citations
“…In analytical or technological research, the concentration of thorium has constituted a special problem, as it accompanies the rare earth elements (REEs), especially uranium [ 135 , 136 ].…”
Section: Thorium Separation And/or Pre-concentrationmentioning
confidence: 99%